Trajectories and influencing factors in adolescent procrastination behavior throughout the COVID-19 pandemic: a four-wave prospective longitudinal study - Wu, Yongmei; Bu, Tianyi; Xie, Yunjia; Wei, Ping; Zhao, Jinxin; Chen, Lu; Qiao, Kexin; Wang, Yan; Yang, Jiarun; Qiu, Xiaohui; Yang, Xiuxian; Zhou, Jiawei; et al. (Frontiers in Psychology, 2023)
Abstract Background: Despite the growing attention to adolescent behavior problems, little is known about the trajectories and factors that influence adolescent procrastination in the COVID-19 pandemic. This study monitors changes in procrastination behavior among Chinese adolescents during the pandemic and identifies vulnerable groups. Methods: A four-wave study in a representative sample of 11-18 years old in China，with baseline data collected in June 2020 (n = 4,156; 49% girls) and follow-ups in June 2020 (n = 3,392; 50% girls), August 2021(n = 2,380; 48% girls) and October 2021 (n = 1,485; 49% girls). Procrastination behavior was assessed using the General Procrastination Scale. Latent growth curve models, latent growth mixture modes and multivariate logistic regression models were used to describe the trajectory of procrastination and identify predictors of deterioration. Results: The proportion and overall trends of adolescent procrastination increased with the pandemic. Higher parental over-protection was a contributing factor to the higher baseline levels leading to the faster growth of adolescent procrastination. The model identified three distinct trajectories of low-increasing (including 2057 participants [49.5%]), moderate-stable (including 1879 participants [45.2%]), and high-decreasing procrastination (including 220 participants [5.3%]). More leisure screen time daily, lower frequency of exercise weekly and dissatisfaction with distance learning were the top three risk factors for moderate-stable and high-decreasing procrastination compared to low-increasing procrastination. Adolescents with higher maternal education were liable to be high-decreasing procrastination than moderate-stable procrastination. Conclusions: The proportion and overall trends of adolescent procrastination increased with the pandemic. The categories of procrastination among adolescents during that time period were probed. Also, the study further clarified the risk factors for severe and moderate procrastination relative to no procrastination. Thus, effective procrastination prevention and intervention strategies need to be implemented to support adolescents–particularly those at risk.